2012
DOI: 10.1007/s00467-012-2101-4
|View full text |Cite
|
Sign up to set email alerts
|

Donor-specific HLA antibodies and graft function in children after renal transplantation

Abstract: Detection of HLA antibodies is common in children after RTx, and this finding, as such, does not predict any deterioration of graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
4
18
5
Order By: Relevance
“…These reports support the implementation of post‐transplant screening for HLA antibodies. This is in contrast to the study performed by Miettinen et al in which the presence of post‐transplant HLA‐DSA was common in children after Tx, not predicting deterioration and poor graft outcome. In addition, Miettinen et al reported no significant difference in GFR decline between DSA‐pos and DSA‐neg patients, while we found that the mean last GFR was significantly lower in the DSA‐pos group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These reports support the implementation of post‐transplant screening for HLA antibodies. This is in contrast to the study performed by Miettinen et al in which the presence of post‐transplant HLA‐DSA was common in children after Tx, not predicting deterioration and poor graft outcome. In addition, Miettinen et al reported no significant difference in GFR decline between DSA‐pos and DSA‐neg patients, while we found that the mean last GFR was significantly lower in the DSA‐pos group.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the study performed by Miettinen et al in which the presence of post‐transplant HLA‐DSA was common in children after Tx, not predicting deterioration and poor graft outcome. In addition, Miettinen et al reported no significant difference in GFR decline between DSA‐pos and DSA‐neg patients, while we found that the mean last GFR was significantly lower in the DSA‐pos group. In our study, the non‐significant difference in the time to 25% GFR decline, in DSA‐pos and DSA‐neg patients, could be explained by the disproportional distribution and low numbers of patients in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, non-DSA against class I (among widely produced HLA antibodies) and, in contrast, DSA against DQ could be readily detected, which corresponds to previous reports. [31][32][33][34] Antibody-binding level based on DQ a/b-combination should be considered, 35 because DQ DSA were reported to be associated with inferior graft outcome. 36,37 Furthermore, the graft condition could be modified by other factors, such as the ability of complement activation and the acquisition of accommodation.…”
Section: Discussionmentioning
confidence: 98%
“…De novo donor-specific antibodies (DSA) can be detected also in pediatric patients and they have been associated with decreased long-term graft function [52,53]. However, contradictory results on the importance of DSA have been published [54].…”
Section: Acute Rejectionmentioning
confidence: 99%